Mendeteksi Kondisi Organ Liver Melalui Citra Iris Menggunakan Teknik Pengolahan Citra Digital - Maxima Ari Saktiono (Muhammadiyah University, Sidoarjo, 2019)
Besides Physical test normally, early detection on the condition of the body by using the image processing of iris is an alternative method to observe the health of human’s body, especially the internal organ of the body. This paper uses Dr. Bernard Jensen’s chart of iris as reference, in which part and how deep is the damage happens in the tissue of iris. Organ disorder is represented by the form of broken tissue of iris. The broken tissue usually seems to be like a hole in certain area in the iris. In this paper, the instrumentation for data mining uses video camera and the software that will be developed uses Visual Basic on image processing programming. In the image of eye, the region of interest is only on the iris, and it will be grabbed by using circle and line equations.The area of Liver organ lies on 07.15 – 07.45 in the third Quadran. After wards, this slice of image is prepared for image processing system. The method that is going to be used in this paper is grey level, enhancing and sobel operator. Then, the output of the system will be compared with physical test to measure the precision on detecting the problem on Liver organ.